Islamic Banking and its Basic Objectives - Heravi, Farid Ahmad (Journal of Social Sciences - Kabul University, 2023)
Islamic banking is a monetary and financial institution that adheres to the rules of Islamic Sharia in all its activities and invests based on the principle of share profit and loss. At first, the idea of Islamic banking began in the forties of the 20th century with the activities of interest-free savings funds in some Islamic countries. The importance of Islamic banking is in the implementation of three strategies of liquidity, benefit and security. Islamic banking has formal objectives such as financial objectives, special objectives for customers, internal objectives, innovative objectives, and effective substantive objectives. These objectives have a significant impact on economic growth; therefore, the daily increasing success of Islamic banking is observed in the world. This article includes an introduction (the history of Islamic banking, its definition, importance and characteristics) and two axes (the first axis is the formal objectives and the second axis is the essential objectives of Islamic banking).